RESILIENCE OF WIFE WORKING VICTIMS OF VIOLENCE AND DIVORCE IN PEKANBARU CITY - Jumni Nelli (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
Abstract: Domestic violence experienced by working women in its various forms and ended in divorce, apparently did not have a negative impact on them and their children. It is interesting to trace the resilience phenomenon of working women in Pekanbaru City to break away from adversity and become strong and great mothers. This research is a phenomenological research about the experiences of working women who experience violence in various forms and are divorced in Pekanbaru City. Data sources were obtained through in-depth interviews and observations using anecdotal record techniques. The research respondents were 4 working women. The theory used is resilience theory from Grotberg about three sources of human resilience, namely "I have, I am and I can". The results of the study found that in general 4 respondents got a source of resilience in the form of "I have", in the form of economic independence, family and colleagues. "I am" resilience, in the form of self-confidence and positive thinking, as well as good understanding and experience of religion. "I can" resilience is the ability of informants to solve their problems and control their emotions. The impact they can influence their children to always do their best. In this study it is understood that if women have economic independence, good religious practice, and family support, of course they are more capable and stronger in experiencing all forms of violence and gender injustice that occur in their families.